Potensi Pengelolaan Wisata Edukasi Pabrik Gula Kebon Agung Di Kabupaten Malang Jawa Timur - Patiung, Yohanes Hessel Salomo; Suryasih, Ida Ayu (JURNAL DESTINASI PARIWISATA; Vol 10 No 1 (2022): VOL 10, NO 1 (2022): (JANUARY - JUNE) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2022.v10.i01.p15, 2022)
The Kebon Agung Sugar Factory has a lot of tourism potential that can be managed as an educational tour. However, its tourism potential has not been managed properly because the Kebon Agung Sugar Factory currently only focuses on carrying out the factory's main function, namely producing sugar. So that the potential for managing educational tourism at the Kebon Agung Sugar Factory is considered important to be a guideline for the company in managing its educational tourism potential. This research uses qualitative methods, namely by conducting observations, interviews, and documentation studies. The technique of determining the informants used purposive sampling. Qualitative data were analyzed using descriptive qualitative analysis and using concepts of tourism potential concepts, educational tourism concepts, tourist attraction concepts, tourism management concepts, sustainable tourism concepts and analyzed using SWOT analysis. The results of this research indicate that the existing conditions of tourism potential at the Kebon Agung Sugar Factory are all managed to carry out and support the main functions of the factory activities. Every tourism potential of the Kebon Agung Sugar Factory is analyzed using a SWOT analysis all of the tourism potential can be managed into an educational tour of the Kebon Agung Sugar Factory. Keyword: Tourism Potential, Educational Tourism, Sugar Factory.